Impact of Immediate and Delayed Error Correction on EFL Learners’ Oral Production: CAF - Rahimi, Afsaneh; Dastjerdi, Hossein Vahid (Richtmann Publishing, 2012)
As the purpose of communication in second/foreign language learning can be complex, fluent and accurate speech,the best type of correcting learners' errors need to be taken into consideration. The aim of this study was to investigate aneffective error correction method (in this case immediate and/or delayed) in developing learners' complexity, fluency andaccuracy in speech. The other aim was to measure the level of anxiety that students experience in the class while the teachercorrects their errors immediately or with some delay. 20 female intermediate EFL learners aged 15 to 20 were chosen from oneof the English language institutes in Isfahan, Iran. The participants were divided into 2 groups of 10. For G1 errors werecorrected immediately and for G2 with some delay, i.e. after finishing their speech during 30 sessions. At the end of the term,each student was asked to discuss one of the topics they had discussed during the term while their voices were recorded andtranscribed later. Measures of accuracy, fluency, and complexity were developed and the results showed that delayed errorcorrection has positive effect on fluency and accuracy but not on complexity. For the second aim, a Foreign Language Anxietyquestionnaire was given to all the participants at the end of the term and the results indicated that G2 with delayed correctionexperienced less anxiety in class.